Perception of increasing or decreasing signal intensity and effects of compression by hearing aids - Palardy, M.-J.; Giguère, C.; De Segovia, C. (Canadian Acoustics, 2003)
Hearing aids are often equipped with non-linear noise reduction algorithms to increase the signal/noise ratio. A typical compression hearing aid will amplify soft sounds and reduce loud sounds. This paper aims to determine whether compression algorithms in hearing aids make intensity changes more difficult to perceive than if no compression is used. In addition, the study also aims to determine whether the effect of a hearing aid on the perception of intensity changes can be predicted by the compression ratio.